2001
DOI: 10.1002/ajmg.1294
|View full text |Cite
|
Sign up to set email alerts
|

Familial benign recurrent vertigo

Abstract: Benign recurrent vertigo (BRV) has been previously linked to migraine but there have been no prior studies of families with BRV. We studied the families of 24 patients who presented to our clinic with BRV and who reported a family history of similar attacks of vertigo. All probands underwent diagnostic evaluation to exclude identifiable causes of recurrent vertigo and they completed a standardized medical questionnaire pertaining to episodic vertigo and the features of migraine. This questionnaire was also sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 20 publications
2
67
1
3
Order By: Relevance
“…Familial occurrence is not uncommon, probably based on an autosomal dominant pattern of inheritance with decreased penetrance in men [ 47 ]. In most patients, migraine headaches begin earlier in life than VM [ 18,41 ].…”
Section: Epidemiology and Demographic Features Of Vestibular Migrainementioning
confidence: 99%
“…Familial occurrence is not uncommon, probably based on an autosomal dominant pattern of inheritance with decreased penetrance in men [ 47 ]. In most patients, migraine headaches begin earlier in life than VM [ 18,41 ].…”
Section: Epidemiology and Demographic Features Of Vestibular Migrainementioning
confidence: 99%
“…It should be noted that headaches do not occur in up to 30% of patients with vestibular migraine. [15][16][17] Between spells, more than 90% of patients exhibit central ocular motor disturbances such as gaze-holding deficits, saccadic smooth pursuit, impaired visual suppression of the vestibulo-ocular reflex, especially downbeat nystagmus, 18 or rarely bilateral internuclear ophthalmoplegia. 19 Some of these patients develop subtle and slowly progressive limb ataxia and postural imbalance later in life.…”
Section: Clinical Features Of Episodic Ataxia Typementioning
confidence: 99%
“…5-8 Familial occurrence is not uncommon, probably based on an autosomal dominant pattern of inheritance with decreased penetrance in men. 26 In most patients, migraine begins earlier in life than vestibular migraine.…”
Section: Clinical Features Demographic Aspectsmentioning
confidence: 99%
“…26 A linkage analysis in a four-generation family with 10 affected individuals mapped the locus for vestibular migraine to chromosome 5q35. 46 In a larger study, familial vestibular migraine was found to be genetically heterogenous with a subgroup linking to chromosome 22q12.…”
Section: Pathophysiologymentioning
confidence: 99%